Influence of seedling age on cucumber (Cucumis sativus L.) production (SAARC Journal of Agriculture, 2016)
Cucumber crop was evaluated for the influence of seedling age on its production during two consecutive years of 2011 and 2012 on experimental area of National Agricultural Research Center (NARC), Islamabad, Pakistan. Nursery of cucumber was raised in polythene tubes under protected structures (walk-in tunnels). Seedling transplantation of three different ages viz., 30, 45 and 60 days were compared with direct seeding in the open field. Seedling transplantation produced fruits earlier (22 days), increased availability period (41 days) as compared to direct seeded crop. Transplantation of 45 and 60 days old seedlings produced higher fruits yield of cucumber with higher gross return and gross margin. The results revealed that transplantation of 45 to 60 days old seedlings was suitable for achieving fruits earlier and profitable cucumber production technology.SAARC J. Agri., 13(2): 214-221 (2015)